Metabolic conditioning for a mixed martial artist - Ribeiro, R. L.; de Oliveira Silva, J. I.; Arruda, A. C. P.; Schwingel, P. A. (Strength and Conditioning Journal, 2016)
This letter is in response to the article titled "A 12-week metabolic conditioning program for a mixed martial artist" by Mikeska JD. Strength Cond J 36: 61-67, 2014.